Exploration and Research of Genealogical Framework of Deep-sea Submersible - Xiaoyun SU; Jun CAO; Zhonghui HU; Xiaoyu ZHAO; Peng YUE (Haiyang Kaifa yu guanli, 2023)
Deep-sea submersible is an important equipment for China to explore the far-reaching sea, the "Jiaolong" sea exploration project was proposed in the "13th Five-Year Plan", which is the overall layout and planning of the national marine cause. Through decades of technological leapfrog development, the "Jiao Long", "Qian Long" series, "Hai Long", "Hai Ma", "Hai Dou", "Hai Yan" and other deep-sea series equipment of different types and depths have been developed, and gradually developed to the lineage. In the future, according to the needs of marine scientific research, the development and utilization of marine resources, and the maintenance of marine rights and interests, more deep-sea equipment that meet the actual requirements will be developed. This paper draws lessons from other high-tech fields, carries out the exploration and research of submarine genealogy, and builds the genealogy framework.